Similar or Different? Value Profile of Secondary Students and Inmate Adolescent Offenders in Peru - Herrera, Dora I. (2017)
In this study, we analyze if the values profiles between institutionalized youngsters (juvenile offenders) and regular school students are distant. A sample of 887 adolescents and youngsters (678 males and 209 females) were assessed. 539 participants were school students from private and public schools and 348 were institutionalized adolescents. The values variable was measured by the Portrait Values Questionnaire (PVQ), created by Schwartz, Melech, Lehmann, Burgess, Harris, & Queens (2001). Results show that both groups had very similar values. The correlation among them was high and positive (r(887) = .84, p < .01). It is concluded that probably values are not the main difference for these two groups. Then, for future preventive interventions, other socio-psychological variables could be prioritized.